Indian theatre and dance traditions - Narayan, Shovana (New Delhi, 2004)
The book Indian Theatre and Dance Traditions covers a wide horizon and provides an insight into the multi dimensional threatical traditions of India that include drama, dance and music, folk and classical.
Keywords: Dance